A new strontium based reactive carbonate composite for thermochemical energy storage. Issue 36 (24th August 2021) - Vieira, Adriana P.; Williamson, Kyran; Humphries, Terry D.; Paskevicius, Mark; Buckley, Craig E.
Abstract : A new reactive carbonate composite based on SrCO3 is presented as a material with high energy density for thermochemical energy storage, being an excellent material to meet the requirement for stable power generation from renewable sources. Abstract : Stable power generation from renewable energy requires the development of new materials that can be used for energy storage. A new reactive carbonate composite (RCC) based on SrCO3 is proposed as a material with high energy density for thermochemical energy storage. SrCO3 –SrSiO3 can promote the thermodynamic destabilisation of SrCO3, making its operating temperature (700 °C) more suitable for concentrated solar thermal power applications. Utilising a eutectic mixture of salts as a catalyst, the reversible carbonation reaction achieves cycle stability of ∼80% of efficiency over multiple cycles. The high volumetric (1878 MJ m −3 ) and gravimetric energy density (500 kJ kg −1 ) of the RCC allows a compact thermal battery to be developed. Additionally, the low cost of SrCO3 makes the RCC a highly competitive alternative energy storage material in terms of cost and efficiency when compared to existing molten salt based energy storage technology.